The Influence of Digital, Social, and Security Literacy on Interest in Using Quick Response Code Indonesian Standard (QRIS) of Millennial and Z Generations in Ponorogo - Ervina Fadhilatul Jannah; Kenlies Era Rosalina Marsudi (Niqosiya: Journal of Economics and Business Research, 2025)
This research is motivated by the rapid development of technology that has encouraged a shift in the payment system from cash to digital, one of which is through the use of the Quick Response Code Indonesian Standard (QRIS). Although digital literacy, environmental influences, and awareness of the importance of digital security among the public, especially the Millennial and Z generations, are quite good, the level of interest in using QRIS is still relatively low. This condition shows the need for strategic efforts from related institutions, such as Bank Indonesia, to increase the adoption of QRIS, especially among the Millennial and Z generations who are one of the main targets in the transformation of the digital payment system. This study aims to test and analyze the influence of digital literacy, social influence, and security on interest in using QRIS among Millennials and Z generations in Ponorogo. The research method used is quantitative with a survey approach. The Millennial and Z generation groups in Ponorogo as the population in this study with a total of 100 respondents. Sampling was done by purposive sampling method. The data processing technique in this study used the SPSS version 23 application. The results showed that partially, digital literacy, social influence, and security which showed that partially the three X variables had a positive and significant effect on the use of QRIS among the Millennial Generation and Z in Ponorogo.